British Fiction After Modernism
XII, 221 p.
Keywords: This collection of essays offers a wide-ranging and provocative reassessment of the British novel's achievements after modernism. The book identifies continuities of preoccupation - with national identity, historiography and the challenge to literary form presented by public and private violence - that span the entire century.